Benito J. Feijoo y el "Machiavel" del "Dictionnaire historique et critique" de Pierre Bayle - Ghia, Walter (Ingenium. Revista Internacional de Pensamiento Moderno y Metodología en Historia de las Ideas, 2015)
This paper closely examines two statements proposed by Feijoo: 1. Machiavelli sets his doctrine in history, therefore his works do not constitute a really original position; 2. Feijoo writes on Machiavelli, but says he never read The Prince entirely. He only read some fundamental quotes, cited by other authors.It is clear that all his references also appear in the voice “Machiavelli” of Pierre Bayle’s Dictionnaire. Moreover, Feijoo’s interpretation is very different from Pierre Bayle’s: in the latter’s view, the work of the Florentine is admirable because Machiavelli breaks with ignorance and hypocrisy revealing the truth of history. According to Feijoo, the Florentine master did not discover anything original and his works merely present the worst examples of governance practices.
Keywords: Machiavelli; Bayle; Feijoo; enlightenment; Catholicism